2022
DOI: 10.34208/mb.v14i2.1666
|View full text |Cite
|
Sign up to set email alerts
|

Factors that affect Fraudulent Financial Reporting

Abstract: The objective of this research is to obtain empirical evidence of the influence of factors that can affect fraudulent financial reporting. Those factors are financial targets, financial stability, external pressure, institutional ownership, number of audit committee members, ineffective monitoring, nature of industry, external auditor quality, the change of auditor, auditor’s opinion, change of directors, proportion of independent commissioner, and numbers of CEO’s picture. The variables used on this research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Moreover, businesses need to have the wherewithal to raise the issue of employees' rationalizing fraud and become accustomed to making this a part of the company culture (Ocansey & Ganu, 2017). This study's findings are consistent with those of Noviana et al (2022), Setiawan &Trisnawati (2022), andSusanti (2018), all of whom concluded that a change in auditors did not result in an increase or decrease in financial statement fraud. Financial statement fraud is affected by auditor turnover, according to Lestari & Bernawati (2020), Anggraini et al (2019), Crisna &Appriwenni (2021), andSari &, although our findings don't agree with those authors' findings.…”
Section: Effect Of Change In Auditor (Audchange) On Fraud Financial S...supporting
confidence: 92%
“…Moreover, businesses need to have the wherewithal to raise the issue of employees' rationalizing fraud and become accustomed to making this a part of the company culture (Ocansey & Ganu, 2017). This study's findings are consistent with those of Noviana et al (2022), Setiawan &Trisnawati (2022), andSusanti (2018), all of whom concluded that a change in auditors did not result in an increase or decrease in financial statement fraud. Financial statement fraud is affected by auditor turnover, according to Lestari & Bernawati (2020), Anggraini et al (2019), Crisna &Appriwenni (2021), andSari &, although our findings don't agree with those authors' findings.…”
Section: Effect Of Change In Auditor (Audchange) On Fraud Financial S...supporting
confidence: 92%
“…The online calculator requires a minimum of 150 words and a maximum of 3000 words from the text. 22 Where possible, all text relevant to gynaecological symptoms was included. Where relevant text exceeded 3000 words, extracts from at least three different sections were included, towards the start, middle and end of the relevant text.…”
Section: Readabilitymentioning
confidence: 99%
“…Management is under pressure to meet financial targets set by shareholders. When these targets cannot be achieved, management may feel compelled to manipulate financial statements to make their performance look better than it is (Anisykurlillah et al, 2023;Fitriana et al, 2024;Setiawan & Trisnawati, 2022). Aggressive financial targets may compel management to engage in financial statement manipulation in order to achieve them (Meihendri et al, 2023;Safiq & Seles, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%